History of the Tangkhul nagas - Shimray, A S W (New Delhi Akansha Publishing House, 2001)
Many books on Nagas had been under taken by foreign writers.But they failed to go deep to the core of Nagas life. The Author, being a Tangkhul Naga himself made a comprehensive in-vestigation on the history of the Nagas-origin,migration,settlement and the
Keywords: Tangkhul (Indic people)-India-History; Ethnology-India; Economics; Community; Community development